Randomized clinical trial of elective resection versus observation in diverticulitis with extraluminal air or abscess initially managed conservatively. Issue 8 (23rd April 2018) - You, K.; Bendl, R.; Taut, C.; Sullivan, R.; Gachabayov, M.; Bergamaschi, R.; ,
Abstract : Background: The aim of this RCT was to determine whether elective resection following successful non‐operative management of a first episode of acute sigmoid diverticulitis complicated by extraluminal air with or without abscess is superior to observation in terms of recurrence rates. Methods: This was a single‐centre, sequential design RCT. Patients were randomized to elective surgery or observation following non‐operative management and colonoscopy. Non‐operative management included nil by mouth, intravenous fluids, intravenous antibiotics, CT with intravenous contrast on arrival at hospital, and repeat CT with intravenous and rectal contrast on day 3 in hospital. The primary endpoint was recurrent diverticulitis at 24 months. Patients with a history of sigmoid diverticulitis, immunosuppression or peritonitis were not included. Results: Of 137 screened patients, 107 were assigned randomly to elective surgery (26) or observation (81), and underwent the allocated intervention after successful non‐operative management. Conservative management failed in 15 patients. Groups were similar in age, sex, BMI, co‐morbidities and colorectal POSSUM. Rates of recurrent diverticulitis differed significantly in the elective surgery and observation groups (8 versus 32 per cent; P = 0·019) at a mean(s.d.) follow‐up of 37·8(8·6) and 35·2(9·2) months respectively. There was also a significant difference in time to recurrence (median 11 versus 7 months; P = 0·015). A total of 28 patients presented with recurrent diverticulitis complicated by extraluminal air and/or abscess (2 elective surgery, 26 observation), all of whom recovered with repeat non‐operative management. Conclusion: The majority of patients observed following conservative management of diverticulitis with local extraluminal air do not require elective surgery. Registration number: NCT01986686 (http://www.clinicaltrials.gov ). Abstract : Conservative management appropriate